Aerosol optical depths and their contributing sources in Taiwan. (January 2017) - Chan, K.L.; Chan, K.L.
Abstract: In this paper, we present a quantitative investigation of the contributions of different aerosols to the aerosol optical depths (AODs) in Taiwan using a global chemical transport model (GEOS-Chem) and remote sensing measurements. The study focus is on the period from June 2012 to October 2013. Five different types of aerosols are investigated: sea salt, dust, sulfate, organic carbon and black carbon. Three of these aerosols, namely sulfate, organic carbon and black carbon, have significant anthropogenic sources. Model simulation results were compared with both ground based sun photometer measurements and MODerate resolution Imaging Spectroradiometer (MODIS) satellite observations. The model data shows good agreement with satellite observations (R = 0.72) and moderate correlation with sun photometer measurements (R = 0.52). Simulation results show the anthropogenic aerosols contribute ∼65% to the total AOD in Taipei, while natural originated aerosols only show a minor impact (∼35%). Among all the aerosols, sulfate is the dominating species, contributing 62.4% to the annual average total AOD. Organic carbon and black carbons respectively contribute 7.3% and 1.5% to the annual averaged total AOD. The annual average contributions of sea salt and dust aerosols to the total AOD are 26.4% and 2.4%, respectively. A sensitivity study was performed to identify the contributions of anthropogenic aerosol sources in each region to the AODs in Taipei. North-East Asia was identified as the major contributing source region of anthropogenic aerosols to Taipei, accounting for more than 50% of total sulfate, 32% of total organic carbon and 51% of total black carbon aerosols. South-East Asia is the second largest contributing source region, contributing 35%, 24% and 34% of total sulfate, organic carbon and black carbon aerosols, respectively. The aerosols from continents other than Asia only show minor impacts to the aerosol load in Taipei. In addition, a case study of a biomass burning episode in South-East Asia during 2013 was investigated. Highlights: Anthropogenic aerosols contribute ∼65% to the AODs in Taipei. Sulfate is the dominating aerosol, contributing to 62% of the total AOD. Emissions in North East Asia have the largest influence to AODs in Taipei. Anthropogenic emissions in South East Asia dominate AODs in Taipei during summer.